Changing banking's DNA : the impact of fintechs on small business lending - Markovich, Sarit; Kolsky, Richard; Snyder, Charlotte (London : Kellogg School of Management, 2021)
This case explores forays by Alibaba, Amazon, and Square into financial services-specifically, lending to small and medium enterprises (SMEs)-and the way their impact and practices differ from those of traditional lenders. The case begins with an overview of the economics of traditional financial institutions' SME lending in the US and China before the entry of fintechs such as Square and big-tech companies such as Amazon and Alibaba. The case then describes how each of these three companies entered the SME lending field, beginning with how Alibaba's Alipay grew into what is now one of the largest fintech companies in the world, Ant Group. Moving to the U.S. market, the case details Amazon's different payment initiatives and Amazon Lending's offerings. Finally, the case recounts Square's entry into the payment market, providing an overview of its Cash App offerings as well as its Square Capital operations.
Originally Published InSarit, M., Kolsky, R. & Snyder, C. (2021). Changing Banking's DNA: The Impact of Fintechs on Small Business Lending. 5-220-250. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Banks and banking -- Case studies; Commercial loans -- Case studies